2008
DOI: 10.1017/s0954394508000070
|View full text |Cite
|
Sign up to set email alerts
|

The role of prosody in morphological change: The case of Hebrew bound numerals

Abstract: The morphological system of cardinal numerals in Modern Hebrew is currently undergoing rapid changes, enabling linguists to unravel the forces shaping the change as it takes place. In the free forms, gender marking on numerals is neutralized by collapsing both masculine and feminine forms into one paradigm, the feminine paradigm. In the bound (definite) forms, an opposite direction is attested, in that at least for some numerals, the masculine forms become more prevalent. The study reported here aims to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In this way, my arguments for animate reference parallel claims made for certain inanimate constituent types (e.g., Meir, 2008;Ravid, 1995). In this way, my arguments for animate reference parallel claims made for certain inanimate constituent types (e.g., Meir, 2008;Ravid, 1995).…”
Section: O R P H O L O G I C a L Va R I A T I O N A N D P R E S C Rmentioning
confidence: 79%
See 3 more Smart Citations
“…In this way, my arguments for animate reference parallel claims made for certain inanimate constituent types (e.g., Meir, 2008;Ravid, 1995). In this way, my arguments for animate reference parallel claims made for certain inanimate constituent types (e.g., Meir, 2008;Ravid, 1995).…”
Section: O R P H O L O G I C a L Va R I A T I O N A N D P R E S C Rmentioning
confidence: 79%
“…Ravid (1995) and Meir (2008), for example, both attempted to experimentally assess whether gender distinctions exist in the grammars of native Hebrew speakers for the free (i.e., indefinite) and bound (i.e., definite) forms of Hebrew cardinal numerals. Ravid (1995) and Meir (2008), for example, both attempted to experimentally assess whether gender distinctions exist in the grammars of native Hebrew speakers for the free (i.e., indefinite) and bound (i.e., definite) forms of Hebrew cardinal numerals.…”
Section: G E N D E R N E U T R a L I Z A T I O N I N H E B R E Wmentioning
confidence: 99%
See 2 more Smart Citations
“…Selective Neutralization In a different study, Meir (2008) analyzed the use of the compound form of the numeral, through assigning production and judgment tasks (see explanation infra). The production test results showed that only two numerals reflected a clear preference for the masculine form regardless of whether the forms were masculine or feminine: 3 (šlošet) and 6 (šešet).…”
Section: 232mentioning
confidence: 99%